Improving Mandatory Vaccination Against Influenza: Minimizing Anxiety of Employees to Maximize Health of Patients. (July 2018) - Benin, Andrea L.; Lockwood, Gina; Creatore, Tracy; Donovan, Donna; Predmore, Maggi; MacArthur, Susan
The objective was to describe qualitatively the attitudes among employees toward mandatory vaccination against influenza to ultimately improve such programs and prevent hospital-acquired influenza. Qualitative interviews were conducted with 21 employees at a freestanding children's hospital. Analysis of interview transcripts used grounded theory and the constant comparative method; codes were iteratively revised and refined as themes emerged. Themes emerged elucidating promoters and concerns. Promoters included a desire to protect self, family, and patients; perception of vaccination as part of professional responsibility; and free vaccination as a benefit from the organization. Concerns included negative feelings surrounding the forced nature and substantial anxiety about the physical injection. Participants expressed a strong desire for a private, compassionate, unhurried environment for the injection. Managing personal anxiety and a desire for privacy emerged as strong concerns among health care workers getting vaccinated at work. This information enabled future improvements in the mandatory vaccination campaign.